2017
DOI: 10.1177/1756287216685027
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol versus other beta blockers in patients with hypertension and erectile dysfunction

Abstract: Erectile dysfunction (ED) impacts over 100 million men worldwide and occurs at a higher incidence in men with hypertension. Beta blockers are one of several antihypertensive drug classes associated with ED. Nebivolol is a beta blocker with vasodilating properties mediated through endothelial release of nitric oxide which facilitates penile erection. Thus, nebivolol may offer an advantage over other beta blockers in the patient with hypertension and ED. A literature search comparing nebivolol with other beta bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 15 publications
(29 reference statements)
2
29
0
3
Order By: Relevance
“…Interestingly, carvacrol or sildenafil treatments were able to reduce SBP to, virtually, the same level. [29,30]. The SHR-S1.5 group presented an improved erectile function, corroborating with reports in the literature [31][32][33].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, carvacrol or sildenafil treatments were able to reduce SBP to, virtually, the same level. [29,30]. The SHR-S1.5 group presented an improved erectile function, corroborating with reports in the literature [31][32][33].…”
Section: Discussionsupporting
confidence: 89%
“…30 However, there are some studies reporting that the use of phosphodiesterase inhibitors, U.S. Food and Drug Administration-approved medications to treat ED, is related to the occurrence of AF. 33 We also recommend using digoxin or calcium channel blocker as an alternative to beta-blockers to avoid the risk of ED. As long as the medication is used appropriately, phosphodiesterase inhibitor would be safe and very useful for this specific subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the use of most selective beta-1 receptor medication is appropriate for AF patients who are at risk of developing ED. 33 We also recommend using digoxin or calcium channel blocker as an alternative to beta-blockers to avoid the risk of ED.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, some CV drugs, such as the beta-blocker, nebivolol (which possesses nitric oxide donor qualities), and the angiotensin receptor blocker (valsartan) may actually improve sexual function. 18,19 Phosphodiesterase type 5 inhibitors (PDE5i) are the first-line treatment for ED, but they must not be used by patients taking nitrates Sexual function • and should be used with caution in patients taking alpha-blockers. 1 In addition to their beneficial effects on the penis, research has shown that sustained treatment with PDE5i may also benefit the heart, via anti-remodelling effects and improvements in cardiac inotropism, independent of afterload changes.…”
Section: Managementmentioning
confidence: 99%